(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The article explores the role, content, and methodological foundations of teaching the subject “Contemporary History of Uzbekistan” in the higher education system. It presents the results of an experimental study conducted based on an innovative author-developed methodology. The paper substantiates pedagogical approaches that contribute to the development of students’ historical thinking, civic stance, national identity, as well as critical and analytical thinking skills. The effectiveness of the methodology is supported by statistical and qualitative analysis, and the prospects for its application to other social and humanitarian disciplines are outlined.